A native annual forb locally excludes a closely related introduced species that co-occurs in oak-savanna habitat remnants. Issue 5 (25th August 2020) - Johnson, Jens C; Williams, Jennifer L
Abstract: Despite the ubiquity of introduced species, their long-term impacts on native plant abundance and diversity remain poorly understood. Coexistence theory offers a tool for advancing this understanding by providing a framework to link short-term individual measurements with long-term population dynamics by directly quantifying the niche and average fitness differences between species. We observed that a pair of closely related and functionally similar annual plants with different origins—native Plectritis congesta and introduced Valerianella locusta —co-occur at the community scale but rarely at the local scale of direct interaction. To test whether niche and/or fitness differences preclude local-scale long-term coexistence, we parameterized models of competitor dynamics with results from a controlled outdoor pot experiment, where we manipulated densities of each species. To evaluate the hypothesis that niche and fitness differences exhibit environmental dependency, leading to community-scale coexistence despite local competitive exclusion, we replicated this experiment with a water availability treatment to determine if this key limiting resource alters the long-term prediction. Water availability impacted population vital rates and intensities of intraspecific versus interspecific competition between P. congesta and V. locusta . Despite environmental influence on competition our model predicts that native P. congesta competitively excludes introduced V. locusta in direct competition across water availability conditions because of an absence of stabilizing niche differences combined with a difference in average fitness, although this advantage weakens in drier conditions. Further, field data demonstrated that P. congesta densities have a negative effect on V. locusta seed prediction. We conclude that native P. congesta limits abundances of introduced V. locusta at the direct-interaction scale, and we posit that V. locusta may rely on spatially dependent coexistence mechanisms to maintain coexistence at the site scale. In quantifying this competitive outcome our study demonstrates mechanistically how a native species may limit the abundance of an introduced invader. Abstract : We observed that closely related annual plants with different origins—native Plectritis congesta and introduced Valerianella locusta —co-occur at community scales but rarely at the scale of direct interactions. We parameterized models of competitor dynamics to quantify niche and average fitness differences between these species with results from an experiment where we manipulated competitor densities and water availability. Our model, corroborated with field data, predicts that P. congesta competitively excludes V. locusta in direct competition across water availability conditions. In quantifying this outcome our study demonstrates mechanistically how a native species may limit abundance of an introduced invader.